“Nakhon Mae-sod” : Trend of the New Pattern of Thai Local Government and Some Observation on the Picture of “Nakhon Pattani” - Phowungprasit, Phaiboon (JOURNAL OF SOUTHERN TECHNOLOGY, 2018)
This paper is about the content of a framework on the Thai local government which will be named “Nakhon Mae-sod” according to the draft of Mae-sod Local Administrative Government Act. On this law, Nakhon Mae-sod is a local government which has both legislative and executive officers from the process of direct election by the voters in that area. This new pattern of local government has authorities which have listed in its law; has budgeting process by itself; as well as ability to make the local law, too. But, it is controlled by the Thai state on some function. Although, a pattern of the Nakhon Mea-sod local government is similar to a pattern of Nakhon Municipality (a biggest municipality type in Thailand) but there are two differences which can be observed olsed. The one is its authorities in the future on ten specific laws which are very extensive. And the other is it has “an advisory and policy development board” who can support or takes care on the administrative process of Nakhon Mae-sod. The other idea that presented in this paper is some observation on the picture of “Nakhon Pattani”. It is the idea of some politician in Thailand. But, an implementation of this idea is very far from now or may be impossible. Because this model of Nakhon Pattani is in the pattern of “autonomous area”; not being a local government. Moreover, there is no guarantee that this model can solve the violent problem in the southern region of Thailand. But if the model of Nakhon Pattani is on a pattern of big local government, it will be possible to implement in this area.